ANALISIS PENGARUH STRATEGI PERUSAHAAN, KARAKTERISTIK PERUSAHAAN, DAN KONEKSI POLITIK TERHADAP MANAJEMEN PAJAK (Studi Empiris Pada Perusahaan Manufaktur Yang Listing di Bursa Efek Indonesia Tahun 2012-2014) - Jannah, Nurriya Miftachul; Sari, Ria Nelly; Hariyani, Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to examine the influence of business strategy, firm characteristics and political connection on tax management. Tax management is a dependent variable in this study that measured by current effective tax rate. Independent variables of this study are business strategy, firm characteristic, and political connection. Firm characteristic that proxy by leverage and capital intensity. The samples of this research are the manufacture firms listed in Indonesian Stock Exchange in 2012-2014. The samples are collected using purposive sampling method and resulted 55 firms become the samples. Data analyzed by classic assumption tests and examination hypothesis by panel data regression. The result shows that there is negative effect of leverage on tax management. Another result shows that there is positive effect of capital intensity on tax management. Business strategy and political connection were not shown to affect tax management.Keywords : tax management, business strategy, firm characteristic, leverage, capital intensity, political connection